BRUSHELLA - G.KARTHIK REDDY, K.SATHISH, P.MAHESH BABU,N.ANKITHA, B.SACHIN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this rapid growth of covid days people are facing unknown diseases. But most of the essential problems are due to water drinking, we may prevent these diseases at our home by using water purifier, but every home can’t provide water purifier. The basic problem was, water will be supplied by water plant stations now a days in cities those water cans should be cleaned properly for our drinking purpose, most of the cleaning of water cans will be done manually, as the person may get tired of cleaning those cans and many not clean it properly. By these circumstances we came up with the rotatory cleaning brush which make less usage of man power so they may not get tired and do their work successfully and do not put people in danger diseases.